Positive Parenting Scale (E2P): Evidence of Validity and Reliability in a Chilean Sample. - Muzzio, Esteban Gómez; Yévenes, Leyla Contreras; Sandoval, José Pezoa (Journal of Child & Family Studies, 2022)
This study investigated the reliability and validity of the new versions of the Positive Parenting Scale (E2P), a series of eight questionnaires designed to assess the frequency of parenting practices in parents of children from 0 months to 17 years of age. Participants were Chilean parents of healthy children (N = 3187) residing in an urban city of Chile. Content validity granted by independent expert judges and confirmatory factor analysis were conducted for each questionnaire. Evidence of convergent and discriminant validity with other scales was also collected. The new versions of E2P Positive Parenting Scale demonstrated robust evidence of structural and content validity, and a pattern of correlations between independent scales and E2P factors consistent with hypothesized expectations, that serve as evidence of convergent and discriminant validity. Reliability of the eight final questionnaires was good to excellent. Considering this evidence, we concluded that the new versions of E2P Positive Parenting Scale are a valid, reliable, feasible, and free access measures for assessing parenting practices in parents of children from 0 months to 17 years in Chilean families. The findings of the confirmatory factor analysis provide support to the theoretical scheme of relational, formative, protective, and reflective parental competencies on which the questionnaire is based. Highlights: Evidence of validity and reliability of the Positive Parenting Scale (E2P) in a sample of 3187 Chilean parents is presented. Eight different versions of the E2P scale were developed to address differences in parenting children of different ages. The results provide robust evidence of structural, content, convergent and discriminant validity, and excellent reliability of all versions of E2P. The findings of the confirmatory factor analysis provide support to the theoretical scheme of relational, formative, protective and reflective parental competencies proposed.